PENATALAKSANAAN FISIOTERAPI PADA KASUS BELL’S PALSY DEXTRA DENGAN MODALITAS ELECTRICAL STIMULATION, MASSAGE EXERCISE DAN MIRROR EXERCISE DI RSUD CIERENG SUBANG - Mesayu Haidaroh, Mesa; Rahman, Ika (Jurnal Infokes, 2023)
Background: Bell’s Palsy is a cranial neuropathy that causes unilateral facial motor neuron paralysis. Objective: To determine the implementation of Physiotherapy in increasing facial muscle strength, reducing the feeling of thickness on the affected side of the face, facilitating facial movement, increasing facial muscle strength, preventing facial muscle atrophy in cases of Bell’s palsy Dexta by using Electrical stimulation, Massage and Therapy modalities Mirror exercise. Results: After 6 treatments using MMT, the patient’s facial muscle strength values ​​increased in M. Orbicularis Oculi T1: 3 and T6: 3. M. Corrugator Supercili: T1: 1 and T6: 1, M. Procerus: T1: 1 and T6: 1, M. Orbicularis Oculi: T1:1 becomes T6: 3, M. Nasalis: T1: 1 becomes T6: 3, M. Depressor Anguli Oris: T1: 1 and T6: 1, M. Zygomaticus Major: T1 : 1 becomes T6: 3, M. Zygomaticus Minor: T1: 1 becomes T6: 3, M. Orbicularis Oris: T1: 1 becomes T6: 2, M. Bucinator: T1: 3 and T6: 3, M. Mentalis: T1 : 1 and T6: 1, M. Risorius: T1: 1 and T6:1, increased ugo fisch scale resting position: T1: 6 and T6: 6, Wrinkling the forehead: T1: 3 and T6: 3, Closing the eyes: T1: 9 becomes T6: 21, Smiling: T1: 9 becomes T6: 21, Whistling: T1: 3 and T6: 3. Conclusion: Electrical stimulation can help cause facial muscle contractions so that it can facilitate movement and increase facial muscle strength. Massage and Mirror exercise can increase the functional ability of facial muscles, reduce stiffness, reduce the feeling of thickness and relax facial muscles.